(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Children with congenital heart disease experience difficulties in house-based management because their caregivers lack the necessary knowledge and understanding of health information. Teaching CHD management to caregivers remains essential for achieving better health results for children while granting caregivers the ability to deliver successful home care. Research documents demonstrate that niche educational approaches produce substantial positive changes in caregiver understanding and competence. Aim: This study aimed to determine the impact of educational intervention programs on health literacy knowledge acquisition about CHD management for caregivers with children diagnosed with CHD. Methods: The research implemented a quasi-experimental design using sixty caregivers divided into two groups, totaling thirty participants in each section. The educational intervention program was delivered to the intervention participants, yet the control participants received no educational materials. Healthcare providers completed the NVS tool as the measure for health literacy assessment, and a designed questionnaire determined their level of knowledge about CHD management. Both pre-test and post-test scores underwent group and individual group analyses to evaluate intervention success. Results: Participants in the intervention experienced notable advancements in their health literacy (p < 0.001), together with increased knowledge about CHD management (p < 0.001). Minimal alteration emerged between pre- and post-tests in both measures for the control group. Data collection showed that intervention group caregivers gained substantial self-assurance in caring for their child at home (p < 0.001), surpassing the levels of the control group. Conclusion: The systematic educational program effectively improved health literacy, knowledge, and confidence levels among caregivers for managing CHD. The research shows that educational programs that provide specific guidance led caregivers to gain more control over child healthcare needs, thus producing better care.